Case report: Keeping a cool head - A delayed open repair of a ruptured TAAA. (January 2021) - Doukas, Panagiotis; Gombert, Alexander; Kotelis, Drosos; Jacobs, Michael
Highlights: Limited resources available during nightshift influence the postoperative outcome. Case: 12 h delayed surgery on an occult ruptured TAAA to bypass the weekend effect ending with the fortunate recovery of the patient. Conclusion: Critical risk assessment in experienced centers during emergency management can justify a delayed procedure to bypass the weekend effect. Abstract: Introduction: The limited resources available for complex surgical procedures during the nightshift can influence the postoperative outcome and are associated with increased complication rates and 30-day mortality. On the other hand, cases of the nightshift are often urgent and demand prompt reaction. Presentation of case: Hereby we report a patient with a ruptured thoracoabdominal aortic aneurysm, who was admitted during nightshift and was operated 12 h later to gain optimal conditions for such a complex surgical treatment and bypass the nightshift-effect. Discussion: A review of the literature shows a significant short-term mortality increase on elective procedures performed during the weekend or during the nightshift, however it remains undecisive on the impact of the weekend-effect on emergent procedures. Conclusion: The fortunate recovering of the patient during his hospital stay as well as in the following months emphasizes the importance of critical risk assessment during emergency management, which may justify a delayed surgical treatment.